Intra-articular osteoid osteoma of the calcaneus: a case report and review - Tomo Hamada, MD; Hidenori Matsubara, MD, PhD; Hiroaki Kimura, MD, PhD; Takao Aikawa, MD; Yasuhisa Yoshida, MD; Hiroyuki Tsuchiya, MD, PhD (Radiology Case Reports, 2016)
Osteoid osteoma of the calcaneus is rare and frequently misdiagnosed as arthritis because of similar symptoms. In addition, radiographic findings may be nonspecific, and magnetic resonance imaging (MRI) may show a bone marrow edema and changes in adjacent soft tissue. A 19-year-old man presented with a 6-month history of persistent pain and swelling in the left hind foot; diagnostic computed tomography and MRI analyses revealed lesions suggesting an intra-articular osteoid osteoma of the calcaneus. Initial MRI did not show specific findings. On operation, the tumor was removed by curettage; pathologic findings demonstrated woven bone trabeculae surrounded by connective tissue, confirming the diagnosis. To the best of our knowledge, MRI scans in all cases of calcaneal osteoid osteoma reported till 3 months after the injury exhibited a nidus. We believe that calcaneal osteoid osteoma should be considered as a differential diagnosis in patients undergoing MRI 3 months after symptom presentation; early computed tomography is critical in diagnosis.